IMPLEMENTATION OF PARTICIPATORY LEADERSHIP STYLE TO INCREASE COVID-19 ERA LEARNING EFFECTIVENESS AT PAUDQU SAHABAT TELADAN KARAWANG - Fajriah Nuraeni; Undang Ruslan W (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2023)
This research was conducted with the aim of knowing how much the influence of participatory leadership style toward decision making in the learning process of Covid-19 era to achieve learning effectiveness, especially in early age. This research used descriptive qualitative method. The data was collected using interview and observation, and then the data was analyzed using method of Miles & Huberman. The findings show, that participatory leadership style can achieve learning effectiveness because in decision making the leader involved subordinates and education policy makers, educational stakeholder.